Impact of PBL, PJBL, and Learning Styles on Geography Achievement - Semi Rombe; Rufi'I Rufi'I; Reza Rachmadtullah (JPG (Jurnal Pendidikan Geografi), 2025)
AbstractThis study aims to analyze the influence of Problem-Based Learning (PBL) and Project-Based Learning (PJBL) models, as well as learning styles (visual, auditory, and kinesthetic), on the geography learning outcomes of Grade X students at SMA Bhakti Mandala Nabire. The background of this research is grounded in the importance of geography instruction that adapts to the development of constructivist learning theories and the diversity of students’ learning styles. This study employs a quantitative approach with a quasi-experimental design using a 3 × 2 factorial model. The sample consists of 30 students divided into two experimental groups based on the learning models and learning styles identified through the VAK questionnaire. Data were collected using pre-tests and post-tests and analyzed using two-way ANOVA. The results reveal that both the learning model and learning style significantly affect students' learning outcomes (p < 0.05). Furthermore, a significant interaction between learning models and learning styles was found in relation to geography learning outcomes. The PJBL model produced more stable outcomes across different learning styles, while PBL proved more effective for visual learners. Visual learners achieved the highest overall scores. These findings highlight the importance of differentiated instructional strategies that align with students' learning characteristics. The study provides both theoretical and practical contributions to the development of adaptive, student-centered geography curricula.